EFFECT OF CASH, RECEIVABLES, INVENTORY, CAPITAL AND FIXED ASSETS TURNOVER ON LIQUIDITY - Wirda Lilia; Rismawantri Regita Risma; Maria Sonti Friska Manullang (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
This study aims to determine the effect of cash turnover, receivable turnover, inventory turnover, working capital turnover and fixed assets turnover on liquidity in textile and garment companies listed on the Indonesia Stock Exchange in 2016-2019. Liquidity is measured using the current ratio. The sampling technique uses purposive sampling with certain criteria and obtained 17 companies with 4 years observation. And used multiple linear regression. The result of this study showed that the simultaneous test of cash turnover, receivable turnover, inventory turnover, working capital turnover, and fixed assets turnover have a significant effect on towards liquidity. Partially individual cash turnover has a positive and insignificant effect, while receivable turnover and fixed assets turnover have a negative and insignificant effect on liquidity. The variable inventory turnover has a positive and significant effect and capital turnover has a negative and significant effect on liquidity in textile and garment companies listed on the Indonesia Stock Exchange in 2016-2019.